2014
DOI: 10.1007/s12011-014-0069-6
|View full text |Cite
|
Sign up to set email alerts
|

Body Condition, Energy Balance and Immune Status of Periparturient Murrah Buffaloes (Bubalus bubalis) Supplemented with Inorganic Chromium

Abstract: Periparturient Murrah buffaloes were used to determine whether body condition, energy balance and immune status are affected by inorganic Cr supplementation. Twenty-four Murrah buffaloes were blocked into four groups having six animals in each group and fed for 60 days pre-partum to 150 days post-partum. Feeding regimen was same in all the groups except that these were supplemented with 0.0, 0.5, 1.0 and 1.5 of Cr per kilogram of dry matter (DM) in the four respective groups. Buffaloes were weighed at fortnigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
6
10
0
Order By: Relevance
“…Increased neutrophil phagocytic activity in the buffalo calves fed a supplement of 1.5 mg Cr/kg DM is in accordance with the findings of DEKA et al (2014) who also reported increased neutrophil phagocytic activity in buffaloes fed 1.5 mg Cr/kg DM periparturient Murrah. A similar result was also reported by KUMAR et al (2015), who found that the addition of inorganic Cr to heat-stressed buffalo calves influenced neutrophil phagocytic activity.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Increased neutrophil phagocytic activity in the buffalo calves fed a supplement of 1.5 mg Cr/kg DM is in accordance with the findings of DEKA et al (2014) who also reported increased neutrophil phagocytic activity in buffaloes fed 1.5 mg Cr/kg DM periparturient Murrah. A similar result was also reported by KUMAR et al (2015), who found that the addition of inorganic Cr to heat-stressed buffalo calves influenced neutrophil phagocytic activity.…”
Section: Discussionsupporting
confidence: 91%
“…Increased neutrophil phagocytic activity was also reported in Cr supplemented transition cattle (KAFILZADEH et al, 2012). However, no effect of dietary Cr supplementation on peripheral neutrophil phagocytic activity was reported by HALDAR et al (2009). The increase in humoral immune response in the 1.0 and 1.5 mg Cr/kg DM supplemented groups is consistent with the findings of KUMAR et al (2015) and DEKA et al (2014) who reported higher levels of TIg and IgG in Cr supplemented periparturient Murrah buffaloes and Murrah buffaloes calves, respectively. WANG et al (2007) stated that pigs supplemented with 200 μg/kg Cr as Cr-Nano had 13.2% and 20.6% higher serum concentrations of IgM and IgG.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations